Formations of European Modernity A Historical and Political Sociology of Europe - Delanty, Gerard (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This book presents a historical and political sociology of European history and society. It offers a critical interpretation of the course of European history looking at the emergence of the idea of Europe and the formation of modernity. Now fully updated, Delanty's second edition features commentary on Brexit, populism, the refugee crisis, and secessionism, as well as additional coverage of colonialism and the wider global context. The book will be in an invaluable resource for advanced undergraduates and postgraduate students of historical sociology, the history of Europe, nations and modernity, political sociology, and political and social theory.